High prevalence of antimicrobial resistance genes in multidrug-resistant-ESBLs-producing Klebsiella pneumoniae post-COVID-19 pandemic - Golnar Rahimzadeh; Shaghayegh Rezai; Ghazal Abbasi; Saman Soleimanpour; Reza Valadan; Laleh Vahedi; Somayeh Sheidaei; Faezeh Sadat Movahedi; Raha Rezai; Mohammad Sadegh Rezai (Iranian Journal of Microbiology)
Background and Objectives: Klebsiella pneumoniae is a common pathogen associated with healthcare-related infections. It is particularly notable for its ability to develop resistance to multiple antibiotics, making treatment challenging. During the COVID-19 pandemic, increased antibiotic use to manage critically ill patients was contributed to the rise of multidrug-resistant Klebsiella pneumoniae. This study evaluated the antibiotic resistance patterns of multidrug-resistant, ESBL-producing Klebsiella pneumoniae in northern Iran after the COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted between September 2022 and October 2023. Clinical samples were collected from patients with nosocomial infections at hospitals in Sari. This study included 114 multidrug-resistant ESBLs-producing Klebsiella pneumoniae isolates. Antimicrobial susceptibility was assessed using broth macro-dilution, and resistance genes were detected by multiplex PCR. Results: Gentamicin, ampicillin-sulbactam, co-amoxiclav, and ceftazidime displayed the lowest activity against multidrug-resistant Klebsiella pneumoniae. In contrast, piperacillin-tazobactam showed the highest activity. The prevalence of resistance genes was as follows: blaTEM (99.12%), blaSHV (74.56%), blaCTX (88.60%), blaIMP (64.04%), acrA -B (92.98%), and OqXA -B (67.54%). Conclusion: This study identified over 50% of antibiotic-resistance genes. Over half of multidrug-resistant Klebsiella pneumoniae isolates showed resistance to antibiotics except piperacillin-tazobactam, which is recommended for treating multidrug-resistant Klebsiella pneumoniae infections.